A comparative study of NSO compounds in high maturity shale. (2nd September 2017) - Ke, ChangWei; Xu, YaoHui; Chang, Xiangchun
ABSTRACT: This research uses high resolution mass spectrometry to compare the NSO compounds in shale extracts. Based on the study of organic hetero-atomic types and distribution, it was found nitrogen compounds were absent in the Cambrian Xiaoyanxi Formation and the Ordovician Yanxi Formation, and the DBE values were lower because of the rocks' high maturity. O2 compounds are the main type present in the Cambrian Xiaoyanxi Formation and the Ordovician Yanxi Formation. Microbial degradation occurred in the Ordovician Yanxi Formation, and processes involving sulfate reducing bacteria might have occurred, represented the lack of O3 compounds, the relatively higher gammacerane index.